Structural glycobiology: applications in organ transplantation - Christiansen, D.; Agostino, Mark; Yuriev, E.; Ramsland, Paul; Sandrin, M. (CRC Press, 2012)
Naturally occurring antibodies (i.e., those existing without known exogenous anti¬gen stimulation) are fundamental in the response to foreign organisms and function in both innate and adaptive immune responses. Indeed, natural preformed antibodies in a recipient are the first immunological barrier for clinical transplantation. To over¬come the chronic shortage of organs available for transplantation, the practice of live donation across the ABO blood group barrier is now performed in many countries (Nydegger et al. 2005; Wu et al. 2003). Furthermore, pig-to-human xenotransplanta¬tion is also being investigated as a viable solution. However, without intervention, the recipient’s natural antibodies would cause hyperacute rejection of the graft. These natural antibodies recognize carbohydrate epitopes on the donor tissue (A or B blood group antigens for allotransplantation; Galα(1-3)Gal [αGal] for xenotransplantation), which are synthesized by closely related members of family 6 glycosyltransferases. In this chapter, we highlight the biochemical, genetic, and immunological features of these clinically important carbohydrate antigens from the enzymes responsible for their synthesis to their molecular interactions with the immune system.